Renal NHE expression and activity in neonatal NHE3- and NHE8-null mice - Pirojsakul, Kwanchai (Am J Physiol Renal Physiol, 2014)
Na(+)/H(+) exchanger (NHE)3 is the predominant NHE on the brush-border membrane of the proximal tubule in adult animals. NHE8 has been localized to the brush-border membrane of proximal tubules and is more highly expressed in neonates than in adult animals. However, the relative role of NHE8 in neonatal renal acidification is unclear. The present study examined if there was a compensatory increase in NHE3 in NHE8-null neonatal mice and whether there was a compensatory increase in NHE8 in NHE3-null neonatal mice. In addition, we examined whether wild-type, NHE3-null, and NHE8-null mice had an increase in NHE activity in response to metabolic acidosis. We found that at baseline, there was comparable renal NHE3 mRNA, total protein, and brush-border membrane protein abundance as in neonatal control and NHE8-null mice. There was comparable renal NHE8 mRNA, total protein, and brush-border membrane protein abundance in NHE3-null neonatal and control mice. Both NHE3- and NHE8-null mice had a comparable but lower rate of NHE activity than control mice. We next imposed metabolic acidosis in wild-type, NHE3-null, and NHE8-null mice. Acidemic NHE8-null mice had an increase in brush-border membrane vesicle NHE3 protein abundance and NHE activity compared with vehicle-treated mice. Likewise, NHE3-null mice had an increase in NHE8 brush-border membrane protein abundance and NHE activity in response to metabolic acidosis. In conclusion, both NHE3 and NHE8 likely play a role in neonatal acidification.